2020
DOI: 10.1101/2020.06.12.147819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overhauling a faulty control in the CDC-recommended SARS-CoV-2 RT-PCR test panel

Abstract: To battle the COVID-19 pandemic, widespread testing for the presence of the SARS-CoV-2 virus is worldwide being employed by specific real-time RT-PCR (rRT-PCR) of viral RNA. The CDC has issued a recommended panel of PCR-based test sets that entail several primer/probe sets that target the SARS-CoV-2 N-gene, but also one that targets the human RNase P gene (h-RP) as a positive control for RNA extraction and/or reverse-transcription (RT) efficacy.We discovered that the CDC-recommended h-RP primer/probe set has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…To control for inhibitors of the reverse transcriptase or PCR enzymes and/or RNase activity in the swab diluent, an aliquot of each swab diluent was spiked with 4 × 10 4 copies of EXO control RNA for subsequent detection with an EXO primer/probe set. While it has been reported that the CDC RNase P primers have the potential to amplify both genomic DNA as well as mRNA (as both primers are in the same exon), the EXO spike-in control utilized in the UW LDT provides a built-in control for successful RT-PCR amplification from a known RNA template [ 9 ]. Inhibition was noted in only 2 samples of 240 tested, 1 negative sample and 1 positive sample tested by the direct approach ( S1B and S2B Tables).…”
Section: Resultsmentioning
confidence: 99%
“…To control for inhibitors of the reverse transcriptase or PCR enzymes and/or RNase activity in the swab diluent, an aliquot of each swab diluent was spiked with 4 × 10 4 copies of EXO control RNA for subsequent detection with an EXO primer/probe set. While it has been reported that the CDC RNase P primers have the potential to amplify both genomic DNA as well as mRNA (as both primers are in the same exon), the EXO spike-in control utilized in the UW LDT provides a built-in control for successful RT-PCR amplification from a known RNA template [ 9 ]. Inhibition was noted in only 2 samples of 240 tested, 1 negative sample and 1 positive sample tested by the direct approach ( S1B and S2B Tables).…”
Section: Resultsmentioning
confidence: 99%
“…Both M and S gene assays have been shown to have high sensitivity [20,21], and their target regions display low sequence variation (S5 Table). Additional improvements to our protocol could include the use of control primers/probe specific to a human RNA transcript (the RPP30 primers/probe described here detect both RNA and genomic DNA) as this would ensure that samples contain intact RNA [22]. However, it should be stressed that any changes to the protocol may also change the sensitivity of SARS-CoV-2 detection, and new protocols should undergo appropriate validation before use for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Both M and S gene assays have been shown to have high sensitivity [20, 21] and their target regions display low sequence variation (Table S5). Additional improvements to our protocol could include the use of control primers/probe specific to a human RNA transcript (the RPP30 primers/probe described here detect both RNA and genomic DNA) as this would ensure that samples contain intact RNA [22]. However, it should be stressed that any changes to the protocol may also change the sensitivity of SARS-CoV-2 detection, and new protocols should undergo appropriate validation before use for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%